Kepemimpinan Kolaboratif dalam Supervisi Paud Sebagai Upaya Membangun Budaya Reflektif Guru Melalui Peer-Coaching - M Nasrudin; Dwi Nuriyah; Aldo Pratama; Mohamad Muspawi; Eva Iryani; Denny Denmar (Universitas Negeri Malang, 2026)
Abstract: Early Childhood Education faces serious challenges in ensuring the quality of learning services that support children’s development optimally. One of the main issues lies in academic supervision practices that remain administrative, hierarchical, and assessment-oriented, thereby failing to effectively promote teachers’ continuous professional development. At the same time, reflective culture among early childhood teachers is still weak, while institutional leadership has not fully provided space for collaboration and active teacher participation in improving instructional quality. This study aims to describe the implementation of collaborative leadership in early childhood supervision through a peer-coaching strategy and to examine its role in fostering a reflective culture among teachers. The study employed a qualitative approach with a descriptive case study design. It was conducted in several early childhood education institutions in Jambi Province that had implemented or were developing collaborative and peer-coaching-based supervision. Participants consisted of 3 to 5 school leaders and 8 to 12 teachers selected purposively. Data were collected through participant observation, in-depth interviews, focus group discussions, and document analysis, and were analyzed using thematic analysis. The findings reveal a shift from traditional directive supervision toward a more dialogic, inclusive, and empowering collaborative supervision model. Peer-coaching was implemented through the CERIA cycle, consisting of Content Focus, Observation, Reflective Collaboration, Inspiring Feedback, and Action and Reinforcement. This cycle encouraged teachers to actively engage in classroom observation, reflective dialogue, constructive feedback, and follow-up improvement plans. Most teachers reported increased reflective awareness, as indicated by new habits such as writing reflective journals, engaging in professional discussions, and voluntarily sharing best practices. However, the implementation still faced several challenges, including limited time, insufficient facilitator training, and the persistence of hierarchical cultural resistance. These findings confirm that the integration of collaborative leadership and peer-coaching has strong potential to strengthen teachers’ reflective culture and improve the quality of supervision and learning in early childhood education in a sustainable manner. Keywords: collaborative leadership, peer-coaching, PAUD supervision, reflective teacher culture, CERIA model Abstrak: Pendidikan Anak Usia Dini (PAUD) menghadapi tantangan dalam menjamin kualitas layanan pembelajaran yang mampu mendukung perkembangan anak secara optimal. Salah satu persoalan utama terletak pada praktik supervisi akademik yang masih cenderung administratif, hierarkis, dan berorientasi pada penilaian, sehingga belum efektif mendorong pengembangan profesional guru secara berkelanjutan. Di sisi lain, budaya reflektif di kalangan guru PAUD juga masih lemah, sementara kepemimpinan lembaga belum sepenuhnya memberi ruang bagi kolaborasi dan partisipasi aktif guru dalam peningkatan mutu pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan penerapan kepemimpinan kolaboratif dalam supervisi PAUD melalui strategi peer-coaching serta mengkaji perannya dalam membangun budaya reflektif guru. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus deskriptif. Penelitian dilaksanakan di beberapa lembaga PAUD di Provinsi Jambi yang telah menerapkan atau sedang mengembangkan supervisi berbasis kolaboratif dan peer-coaching. Partisipan terdiri atas 3 sampai 5 kepala PAUD dan 8 sampai 12 guru yang dipilih secara purposive. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam, focus group discussion, dan studi dokumentasi, lalu dianalisis secara tematik. Hasil penelitian menunjukkan adanya pergeseran dari supervisi tradisional yang direktif menuju supervisi kolaboratif yang lebih dialogis, inklusif, dan memberdayakan. Peer-coaching dilaksanakan melalui siklus CERIA, yaitu Content focus, Observation, Reflective collaboration, Inspiring feedback, dan Action and reinforcement. Penerapan siklus ini mendorong guru untuk terlibat aktif dalam observasi, refleksi, pemberian umpan balik, dan tindak lanjut perbaikan pembelajaran. Sebagian besar guru melaporkan peningkatan kesadaran reflektif, yang ditunjukkan melalui kebiasaan menulis jurnal refleksi, berdiskusi, dan berbagi praktik baik. Meski demikian, implementasi masih menghadapi kendala berupa keterbatasan waktu, kurangnya pelatihan fasilitator, dan resistensi budaya hierarkis. Temuan ini menegaskan bahwa integrasi kepemimpinan kolaboratif dan peer-coaching berpotensi memperkuat budaya reflektif guru serta meningkatkan mutu supervisi dan pembelajaran PAUD secara berkelanjutan. Kata kunci: kepemimpinan kolaboratif, peer-coaching, supervisi PAUD, budaya reflektif guru, model CERIA